REKOMENDASI ILUSTRASI CERITA ALKITAB: SAMARIA BAIK HATI - Valentina, Anny; Nathania, Gracella; Indigo, Michelle; Ivanson, Kevin Matthew (Jurnal Serina Abdimas, 2024)
Literacy is an essential skill in processing and understanding information through reading and writing, and it also plays a role in the spiritual development of individuals. In Indonesia, the level of literacy remains low. This low interest in literacy is exacerbated by factors such as limited access and the impact of the COVID-19 pandemic, particularly in the context of distance learning. One promising approach to improving literacy is the use of visual illustrations with a narrative approach, which can help enhance children’s understanding and memory retention of texts. This study aims to develop and implement visual media that supports the enhancement of children’s literacy, particularly through the translation and visualization of biblical stories, such as in the Minahasa language. The methods used include observation, literature review, and interviews to identify issues, design visual solutions, and test their effectiveness through the “Bible in Use” program. This program encourages children to read, understand, and memorize Bible verses with the aid of visual illustrations designed in both soft copy and hard copy formats. The results of the study show that the use of visual illustrations and narrative approaches can increase children’s engagement and understanding, as well as strengthen their memory skills. The implementation of this strategy successfully contributes positively to enhancing reading interest and literacy among children, especially in the Minahasa region. Therefore, this narrative visualization of the Bible has the potential to be an effective model for improving literacy in Indonesia. ABSTRAK Literasi merupakan keterampilan penting dalam memproses dan memahami informasi melalui membaca dan menulis, serta berperan dalam perkembangan spiritual individu. Di Indonesia, tingkat literasi masih rendah, Rendahnya minat literasi ini diperparah oleh faktor-faktor seperti akses terbatas dan dampak pandemi COVID-19, terutama dalam konteks pembelajaran jarak jauh. Salah satu pendekatan yang menjanjikan untuk meningkatkan literasi adalah penggunaan ilustrasi visual dengan pendekatan naratif, yang dapat membantu meningkatkan pemahaman dan daya ingat anak-anak terhadap teks. Penelitian ini bertujuan untuk mengembangkan dan mengimplementasikan media visual yang mendukung peningkatan literasi anak-anak, khususnya melalui penerjemahan dan visualisasi cerita Alkitab, seperti dalam bahasa Minahasa. Metode yang digunakan mencakup observasi, studi literatur, dan wawancara untuk mengidentifikasi masalah, merancang solusi visual, serta menguji efektivitasnya melalui program “Bible in Use.” Program ini mengajak anak-anak untuk membaca, memahami, dan menghafal ayat-ayat Alkitab dengan bantuan ilustrasi visual yang dirancang dalam format soft copy maupun hard copy. Hasil penelitian menunjukkan bahwa penggunaan ilustrasi visual dan pendekatan naratif mampu meningkatkan daya tarik dan pemahaman anak-anak, serta memperkuat kemampuan mengingat mereka. Implementasi strategi ini berhasil memberikan kontribusi positif terhadap peningkatan minat baca dan literasi di kalangan anak-anak, terutama di wilayah Minahasa. Dengan demikian, visualisasi naratif Alkitab ini berpotensi menjadi model yang efektif dalam meningkatkan literasi di Indonesia.